The Influence of Advertising Effectiveness on Consumer Purchase Decisions in Wardah Medan Instagram social media Cosmetic Advertising - Sylvani Dewi; Felicia Winata; Elly Romy; Kiki Goslim; Wenny Wenny (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to identify the effectiveness of wardah advertisements through Instagram social media on active @wardahbeauty followers on Instagram. Consumers who use social media Instagram @wardah beauty are active with a total of 92 followers. The data analysis technique used in this study is a validity test, reliability using SPP version 20.0 Based on the results of the study, the validity and reliability test of the questionnaire for each statement item was declared valid and the results obtained were that the independent variable, namely advertising effectiveness (X) had a positive and significant influence on the dependent variable, namely purchase decision (Y), this is indicated by the tcount value = 5.603 and ttable = 2.01537 then tcount > ttable, so Ho is rejected and Ha is accepted. Based on simple linear regression calculations, the regression equation Y = 25.982 + 0.531X + e means that every time there is an increase in the purchasing decision variable by 0.531, it will affect the effectiveness of advertising. The coefficient of determination (R2) is 0.416 (41.6%). So it can be said that 41.6% of the dependent variable, namely advertising effectiveness in this study, can explain purchasing decisions while the remaining 58.4% is influenced by other variables outside the variables studied.